2022
DOI: 10.3389/fpubh.2022.817717
|View full text |Cite
|
Sign up to set email alerts
|

Disempowered Mothers Have Undernourished Children: How Strong Is the Intrinsic Agency?

Abstract: ObjectiveUndernutrition is one of the leading causes of morbidity and mortality among under-five children, particularly in low-and-middle-income countries. Since women, including mothers, are the primary caregivers of their children, their empowerment status can inherently influence children's nutritional status. Empowerment is, mainly, an intrinsic agency developed as an affective domain trajectory or attitude that guides the skill or behavior. This study aimed to assess the association between women's empowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…In Pakistan, mothers’ higher levels of education and employment status enable them to directly engage in household decision-making and buy high-quality dietary food for children, which is positively related to the nutritional status of children [ 23 ]. Similarly, a cross-sectional study from the rural Kaski district of Nepal documented that intrinsic factors such as maternal education and community membership associated with maternal empowerment reduced the likelihood of having underweight and stunted children [ 28 ]. In Bangladesh, Rahman et al [ 26 ] found that mothers’ participation in household decision-making is associated with lower odds of childhood malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, mothers’ higher levels of education and employment status enable them to directly engage in household decision-making and buy high-quality dietary food for children, which is positively related to the nutritional status of children [ 23 ]. Similarly, a cross-sectional study from the rural Kaski district of Nepal documented that intrinsic factors such as maternal education and community membership associated with maternal empowerment reduced the likelihood of having underweight and stunted children [ 28 ]. In Bangladesh, Rahman et al [ 26 ] found that mothers’ participation in household decision-making is associated with lower odds of childhood malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some of the factors related to the socio-cultural belief system of the society are also taken as the determinant factors for women's empowerment, such as traditional and religious belief systems (Alatinga et al, 2021) and notions about the transactional sex (Wamoyi et al, 2011). Furthermore, indices such as Women's Empowerment Index (WEI), Abridged Women's Empowerment in Nutrition Index (A-WENI), Women's Empowerment in the Agricultural Index (WEAI), Abbreviated Women's Empowerment in the Agricultural Index (A-WEAI) and Project-level Women's Empowerment in the Agricultural Index (Pro-WEAI) are also used to measure the empowerment of women (Bonis-Profumo et al, 2022;Cunningham et al, 2015;Kirkwood et al, 2021;Poudel et al, 2022;Saha & Narayanan, 2022).…”
Section: Thematic Slr For the Aggregated Clusters 1 3 6 Andmentioning
confidence: 99%
“…The nutritional status of children is conceptualized in terms of children's dietary diversity (CDD) (Badiane et al, 2021;Bonis-Profumo et al, 2022;Cunningham et al, 2019;Egbuonyet al, 2021). However, weight for age (Imai et al, 2014) and height for age (Badiane et al, 2021;Cunningham et al, 2015Cunningham et al, , 2019Debela et al, 2021;Imai et al, 2014;Tome et al, 2021), wasting (Tonguet-Papucci et al, 2015), stunting of children (Poudel et al, 2022;Rabaoarisoa et al, 2017) and body composition of children measured as fat-free mass (Badiane et al, 2021) are also indicators. Finally, we proceed to the broader theme for impact assessment related to maternal and child health, including clusters 4 and 5.…”
Section: Thematic Slr For the Aggregated Clusters 2 Andmentioning
confidence: 99%
See 2 more Smart Citations